2001
DOI: 10.1080/713846811
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus Induces Vaginal Tissue Fibrosis by TGF-beta; 1 Expression in the Rat Model

Abstract: The commonly reported sexual problem in women with diabetes mellitus is lack of vaginal lubrication. It is our hypothesis that reduced vaginal lubrication in diabetic women may result from the structural changes of the vagina. The aim of this study was to investigate in the diabetic rat model the vaginal structures using histochemistry and the expression of TGF-beta 1 using immunohistochemistry. Twenty female Sprague-Dawley rats (200-210 g) were divided into two groups: control and experimental. The experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 18 publications
2
38
0
Order By: Relevance
“…to electrical stimulation of nerves (EFS), to NO donors, and to calcitonin gene-related peptide (CGRP)] and the contractile response of vaginal tissue to norepinephrine and to EFS. 65 Other rat studies have indicated that diabetes causes a significant decrease in nervestimulated clitoral and vaginal blood flow, induces diffuse fibrosis of the clitoris and the vaginal tissue, and reduces muscular layer and epithelial thickness in the vagina, 63,64,66 thus impairing sexual response. Studies in humans, using vaginal plethysmography as an objective measure of physiological arousal, have found an association between diabetes and decreased vaginal lubrication.…”
Section: Pathogenesis Of Female Sexual Dysfunction In Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…to electrical stimulation of nerves (EFS), to NO donors, and to calcitonin gene-related peptide (CGRP)] and the contractile response of vaginal tissue to norepinephrine and to EFS. 65 Other rat studies have indicated that diabetes causes a significant decrease in nervestimulated clitoral and vaginal blood flow, induces diffuse fibrosis of the clitoris and the vaginal tissue, and reduces muscular layer and epithelial thickness in the vagina, 63,64,66 thus impairing sexual response. Studies in humans, using vaginal plethysmography as an objective measure of physiological arousal, have found an association between diabetes and decreased vaginal lubrication.…”
Section: Pathogenesis Of Female Sexual Dysfunction In Diabetesmentioning
confidence: 99%
“…Studies in animals have indicated that diabetes, by inducing structural and functional changes in the female genital tract, may result in impaired arousal and orgasmic sexual response. 63,64 In a rat model of streptozotocin-induced diabetes it has been shown that diabetes impaired the relaxation responses of the vaginal tissue to almost all transmitter systems [i.e. to electrical stimulation of nerves (EFS), to NO donors, and to calcitonin gene-related peptide (CGRP)] and the contractile response of vaginal tissue to norepinephrine and to EFS.…”
Section: Pathogenesis Of Female Sexual Dysfunction In Diabetesmentioning
confidence: 99%
“…HuC/HuD,anti-human neuronal protein HuC/HuD identifies all neuronal cell bodies in the ganglion; NADHd, diaphorase positive [520]. These are important findings because TGF-β system mediated also diabetic renal hypertrophy and fibrosis build-up due to the extracellular matrix production [521,522], and TGF-β1 was found to induce vaginal tissue fibrosis in animal model [523], while the beta cell hypertrophy, beta cell damage and fibrosis, with reduction in insulin secretion, is characteristic for patients with T2DM [7]. In this context, a significant increase of plasma TGF-β1 levels caused by latent T. gondii infection may play a key role in development of pancreatic islet beta cell abnormalities found in T2DM.…”
Section: T Gondii Infectionmentioning
confidence: 78%
“…Animals were fasted for 18-24 h and STZ (65 mg/kg) in 0.02 M citrate saline buffer was administered intraperitoneally, as described previously (Giraldi et al 2001;Park et al 2001;Usta et al 2003). The control group animals received citrate buffer only.…”
Section: Diabetes Inductionmentioning
confidence: 99%